First-Principles Study on Interfacial Triboelectrification Between Water and Halogen-Functionalized Polymer Surfaces - Taili Tian; Bo Zhao; Yimin Wang; Shifan Huang; Xiangcheng Ju; Yuyan Fan (Lubricants)
Contact electrification (CE), or triboelectrification, is an electron transfer phenomenon occurring at the interface between dissimilar materials due to differences in polarity, holding significant research value in tribology. The microscopic mechanisms of CE remain unclear due to the complex coupling of multiple physical processes. Recently, with the rise of triboelectric nanogenerator (TENG) technology, solid–liquid contact electrification has demonstrated vast application potential, sparking considerable interest in its underlying mechanisms. Emerging experimental evidence indicates that at water–polymer CE interfaces, the process involves not only traditional ion adsorption but also electron transfer. Halogen-containing functional groups in the solid material significantly enhance the CE effect. To elucidate the microscopic mechanism of water–polymer CE, this study employed first-principles density functional theory (DFT) calculations, simulating the interfacial electrification process using unit cell models of water contacting polymers. We systematically and quantitatively investigated the charge transfer characteristics at interfaces between water and three representative polymers with similar backbones but different halogen-functionalized (F, Cl) side chains: fluorinated ethylene propylene (FEP), polyvinyl chloride (PVC), and polytetrafluoroethylene (PTFE), focusing on evaluating halogen’s influence and mechanism on interfacial electron transfer. The results reveal that electron transfer is primarily governed by the energy levels of the polymer’s lowest unoccupied molecular orbital (LUMO) and highest occupied molecular orbital (HOMO). Halogen functional groups modulate the material’s electron-donating/accepting capabilities by altering these frontier orbital energy levels. Consequently, we propose that the critical strategy for polymer chemical modification resides in lowering the LUMO energy level of electron-accepting materials. This study provides a novel theoretical insight into the charge transfer mechanism at solid–liquid interfaces, offers guidance for designing high-performance TENG interfacial materials, and holds significant importance for both the fundamental theory and the development of advanced energy devices.